1993
DOI: 10.1142/s0217751x93000928
|View full text |Cite
|
Sign up to set email alerts
|

On Possible Generalizations of Field-Antifield Formalism

Abstract: A generalized version is proposed for the field-antifield formalism. The antibracket operation is defined in arbitrary field-antifield coordinates. The antisymplectic definitions are given for first-and second-class constraints. In the case of second-class constraints the Dirac's antibracket operation is defined. The quantum master equation as well as the hypergauge fixing procedure are formulated in a coordinate-invariant way. The general hypergauge functions are shown to be antisymplectic first-class constra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
139
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(141 citation statements)
references
References 18 publications
(31 reference statements)
2
139
0
Order By: Relevance
“…At the same time, in the present approach the gauge-independence is encoded in BRST transformations controlled by generating equations imposed on the entire gauge part of the quantum action, whereas in the framework of [8] this role is played by unimoduar involution relations imposed on hypergauge functions. Despite the formal similarity between the vacuum functional (32) proposed by the present study and the ansatz (33) suggested by [8] the two methods appear to be independent from each other, being different generalizations of the BV method.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…At the same time, in the present approach the gauge-independence is encoded in BRST transformations controlled by generating equations imposed on the entire gauge part of the quantum action, whereas in the framework of [8] this role is played by unimoduar involution relations imposed on hypergauge functions. Despite the formal similarity between the vacuum functional (32) proposed by the present study and the ansatz (33) suggested by [8] the two methods appear to be independent from each other, being different generalizations of the BV method.…”
Section: Discussionmentioning
confidence: 96%
“…At the same time, in the present approach the gauge-independence is encoded in BRST transformations controlled by generating equations imposed on the entire gauge part of the quantum action, whereas in the framework of [8] this role is played by unimoduar involution relations imposed on hypergauge functions. Despite the formal similarity between the vacuum functional (32) proposed by the present study and the ansatz (33) suggested by [8] the two methods appear to be independent from each other, being different generalizations of the BV method. However, as is seen from the above comparison, the vacuum functional (32) proposed by the present study becomes identical, in the particular case of linear dependence on the Lagrange multipliers, with the first-level vacuum functional [8] considered in the case of a trivial integration measure and vanishing structure functions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The quantization rules [1] combine, in terms of superfields, a generalization of the "firstlevel" Batalin-Tyutin formalism [5] (the case of reducible hypergauges is examined in [6]) and a geometric realization of BRST transformations [7,8] in the particular case of θ-local superfield models (LSM) of Yang-Mills-type. The concept of an LSM [1,2,4], which realizes a trivial relation between the even t and odd θ components of the object χ = (t, θ) called supertime [9], unlike the nontrivial interrelation realized by the operator D = ∂ θ + θ∂ t in the Hamiltonian superfield N = 1 formalism [10] of the BFV quantization [11], provides the basis for the method of local quantization [1,2,4] and proves to be fruitful in solving a number problems that restrict the applicability of the functional superfield Lagrangian method [12] to specific gauge theories.…”
Section: Introductionmentioning
confidence: 99%